1999
DOI: 10.1159/000022519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Haemostatic System during Ketoacidotic Deterioration of Diabetes mellitus

Abstract: Clinical observations have indicated the frequent development of thrombotic complications during diabetic ketoacidosis (DKA). This study aimed to examine whether haemostatic changes that could lead to a thrombotic tendency occur during ketoacidosis. Plasma levels of in vivo haemostatic markers reflecting activation degrees of the coagulation system, fibrinolytic system, platelets and endothelium were assayed in 34 patients with DKA, both at diagnosis and 1 week after recovery. We found coagulation system and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…One of the postulates as to the cause of the procoagulant state is that DKA represents an inflammatory disease with increased C-reactive protein, cytokines and complement. 16 This is reflected in abnormal endothelial function with raised von Willebrand Factor, tissue plasminogen activator and cellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…One of the postulates as to the cause of the procoagulant state is that DKA represents an inflammatory disease with increased C-reactive protein, cytokines and complement. 16 This is reflected in abnormal endothelial function with raised von Willebrand Factor, tissue plasminogen activator and cellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these researchers reported the hemostatic alterations in 34 patients with uncomplicated diabetic ketoacidosis. 32 The authors again found evidence of endothelial injury/activation, platelet and coagulation system activation and decrease in fibrinolysis during diabetic ketoacidosis. There was significant improvement after 1 week with platelet activity returning to normal.…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of these findings of enhanced coagulability, these authors raised the idea of prophylactic anticoagulation in patients with DKA. 31,32 We cared for three patients admitted with severe hyperglycemia who suffered massive pulmonary embolism within 72 hours of presentation. None had prior venous thromboembolism or cardiopulmonary symptoms or signs on presentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of increased thrombin-antithrombin complex, plasma factor VII coagulant activity, and D--dimers, besides increased intima-media thickness of the carotid artery were found in children with T1DM (6,7).…”
Section: Discussionmentioning
confidence: 96%